1998
DOI: 10.1136/oem.55.10.657
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to crystalline silica and risk of sarcoidosis.

Abstract: Objectives-The possibility of an association between exposure to silica and autoimmune diseases has recently come under discussion. In the following casereferent study, a cohort exposed to diatomaceous earth and cristobalite provided an opportunity to evaluate such an exposure with reference to sarcoidosis. Methods-The inhabitants of a district served by a single healthcare centre and a hospital formed the study base. A diatomaceous earth plant is located in this community and the medical institutions are resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 10 publications
0
84
1
1
Order By: Relevance
“…Inhaling inorganic substances can induce sarcoidosis, as Rafnsson and colleagues reported [43] Exposure to metals such as beryllium, titanium, aluminum, and zirconium is discussed as a trigger for sarcoidosis. The penetrance of risk is governed by two factors: genetic background and intensity of exposure [44][45][46][47][48].…”
Section: Metalmentioning
confidence: 99%
“…Inhaling inorganic substances can induce sarcoidosis, as Rafnsson and colleagues reported [43] Exposure to metals such as beryllium, titanium, aluminum, and zirconium is discussed as a trigger for sarcoidosis. The penetrance of risk is governed by two factors: genetic background and intensity of exposure [44][45][46][47][48].…”
Section: Metalmentioning
confidence: 99%
“…In a fourth case report, a patient presented with diffuse pulmonary granulomatosis, with sarcoid-like epithelioid granulomas and helper T-lymphocyte alveolitis [54]. The individual's occupational history suggested that his illness could be related to his work; he had worked as a chemist for eight years in a catalyst fabrication plant where he was exposed to large amounts of aluminum powders and iron and smaller quantities of copper, zinc, nickel, chromium, manganese, cobalt, molybdenum, vanadium, palladium, and silica.…”
Section: Pulmonary Alveolar Proteinosismentioning
confidence: 99%
“…These would include exposures to silica, cristobalite, aluminum compounds, barium compounds, beryllium, cobalt, copper, gold, titanium, zirconium, lanthanide metals, talc, glass fibers, rock wool, mixed dust, woodstoves, and firefighting [28,[53][54][55][56][57][58][59][60][61][62][63].…”
Section: Pulmonary Alveolar Proteinosismentioning
confidence: 99%
“…Exposure to crystalline silica can also increase the risk of developing lung cancer (Hughes et al, 2001;Knutsson et al, 2000;Peretz et al, 2006). Other studies have shown a link between crystalline silica exposure and the development of autoimmune disorders (Calvert et al, 2003;Rafnsson et al, 1998;Rosenman & Zhu, 1995). Diseases associated with crystalline silica exposure are usually incurable but are preventable.…”
Section: Introductionmentioning
confidence: 99%